A&T Burkina Faso Maternal Nutrition Endline Survey 2021: Recently Delivered Women - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition and infant and young child feeding practices. In Burkina Faso, A&T developed and tested an intensive package of maternal nutrition interventions to be integrated into existing ANC services delivered through government health facilities. These included intensified counseling and support on dietary diversity and quality during pregnancy, iron-folic acid (IFA) supplements consumption, importance of ANC and increasing the number of visits, adequate weight-gain monitoring, and early initiation of and exclusive breastfeeding. This dataset is part of a survey that was conducted to gather endline data for the impact evaluation of the interventions.